2011
DOI: 10.1589/jpts.23.617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6 Months Combined Functional Training on Muscle Strength, Postural Balance and Gait Performance in Community-dwelling Individuals with Chronic Stroke Hemiplegia

Abstract: Abstract. [Purpose] We conducted a noncontrolled intervention study in community-dwelling individuals with chronic stroke hemiplegia as subjects to examine the effectiveness of a 6 month low-frequency combined functional training program on enhancing factors related to physical performance, such as leg muscle strength, postural balance, and gait function. We also examined whether medium-term changes in physical performance correlated with time from stroke onset or degree of hemiplegia. [Subjects and Methods] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Recent studies suggested that walking-related indexes were improved by intensive gait rehabilitation or several rehabilitation programs for chronic stroke survivors 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ) . Gait speed has been recognized as an indicator of gait performance 35 ) , and it is composed of step length and cadence 36 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that walking-related indexes were improved by intensive gait rehabilitation or several rehabilitation programs for chronic stroke survivors 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ) . Gait speed has been recognized as an indicator of gait performance 35 ) , and it is composed of step length and cadence 36 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Using functional magnetic resonance imaging (fMRI), Lotze et al showed that the activity of the primary motor cortex is more significantly increased after active training compared with passive activity 27 ) . In stroke patients, deterioration of gait ability is primarily caused by a lack of voluntary control of muscle contraction, thereby resulting in the loss of ability to control the timing and intensity of muscular activity 1 ) . Selective muscular control, however, can be induced by external cues, such as vibratory stimulation, which cause active muscular contraction.…”
Section: Discussionmentioning
confidence: 99%
“…After a stroke, gait is an important determinant of functional ability in the activities of daily living and for an independent life 1 ) . In general, stroke patients continue to have walking difficulties, including reductions in their gait velocity and endurance caused by the weakness of muscles and deterioration of voluntary control function 2 ) .…”
Section: Introductionmentioning
confidence: 99%
“…ANTONIO MUÑOZ-LLERENA, JESÚS FERNÁNDEZ-GAVIRA, LUISA VÉLEZ COLÓN, JERÓNIMO GARCÍA- FERNÁNDEZ ------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------ Hashidate, Shiomi & Sasamoto (2011) examined the effectiveness of a functional training program combined with low intensity on factors related to physical endurance, such as balance, leg strength, or motor function. Twenty-two participants took part in an intervention consisting of one to two sessions per week during six months of combined functional training.…”
Section: Jpes ®mentioning
confidence: 99%